Micah 1, an apt introduction to power talks - Wessels, W. J. (Verbum et ecclesia, 1998)
Power and the abuse of it, is often an integral part of discussions in any society. The prophets of the Old Testament felt strongly about this issue and often spoke out against the abuse of power and the suffering caused by it. Micah particularly addresses this issue in chapters 2 and 3. He blames the leaders in society, who should look out for the ordinary people, that they in particular are guilty of this transgression. In chapter 1 Micah proclaims Yahweh as the sovereign power who they should take note off. On the very basis of Yahweh's sovereign power he then proclaims oracles of judgment on the people of Judah. Micah 1 seems to form an apt introduction to the talks of the abuse of power in the society of Judah.